Literature Review: Efektivitas Terapi Musik Klasik Terhadap Gangguan Mental Pada Anak Hingga Lansia - Keissa Nazelina; Ati Kusmawati; Kesya Syafinatunnida; Vinca Anidya (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
The background of this literature review study is the many people still suffer from mental illnesses, and the number of people who suffer from them is growing every year. Types of mental disorders such as depression, anxiety, stress, hallucinations, and others. The purpose of this literature is to see how efficient Classical Music Therapy is at lowering the rate of mental problems in people of all ages, from children to the elderly. The method of literature review review was obtained using the keywords